Repair Integrity and Functional Outcomes After Arthroscopic Suture Bridge Subscapularis Tendon Repair - Shibayama, Kazuhiro; Sugaya, Hiroyuki; Matsuki, Keisuke; Takahashi, Norimasa; Tokai, Morihito; Onishi, Kazutomo; Tanaka, Sakae (Arthroscopy, 2018)
This retrospective study aimed to report repair integrity and clinical outcomes after arthroscopic suture bridge subscapularis (SSC) tendon repair. The subjects included 101 shoulders subjected to arthroscopic suture bridge repair for full-thickness SSC tear with a minimum of a 2-year follow-up. There were 57 men and 44 women with a mean age of 66 years (range, 32-85 years). The mean follow-up was 30 months (range, 24-71 months). Tenotomy or tenodesis was performed for the long head of the biceps in all cases. All patients were assessed for active range of motion; belly-press and bear-hug tests; University of California, Los Angeles score; and American Shoulder and Elbow Surgeons score preoperatively and at the final follow-up. Repair integrity and fatty degeneration of the SSC muscle were evaluated with magnetic resonance imaging at a mean 14 months (range, 12-58 months) after surgery. Flexion, internal rotation, and both functional scores significantly improved after surgery. Retears were found in 5 shoulders (5%). The shoulders with a retear showed significantly inferior functional scores compared with the intact shoulders. Fatty degeneration was significantly improved in the intact group, whereas there was no significant improvement in the retear group. Both belly-press and bear-hug test scores significantly improved after surgery; however, weakness persisted in shoulders with higher grade preoperative fatty degeneration even after successful repair. Arthroscopic suture bridge repair for SSC tears yielded good clinical outcomes and a very low retear rate, even for larger tears or shoulders with higher grade fatty degeneration. Fatty degeneration of the SSC muscle improved after successful repair, although internal rotation weakness persisted in shoulders with higher grade preoperative fatty degeneration. Arthroscopic suture bridge repair is a promising procedure for treating SSC tears. Level IV, case series study.